2014
DOI: 10.3892/ijo.2014.2732
|View full text |Cite
|
Sign up to set email alerts
|

Real-time quantitative RT-PCR detection of circulating tumor cells from breast cancer patients

Abstract: Circulating tumor cells (CTCs) were recognized as novel tumor biomarker for prognostic and predictive purposes in various cancers. Various detection technologies and devices have been developed to enumerate and characterize CTCs. Most of those approaches are based on the positive enrichment strategy and immunocytological techniques. However, the sensitivity of these approaches proved to be limited in metastatic tumors and the detection of early tumor cell dissemination was problematic. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…[30][31][32] RT-PCR analysis of CTCs signature, enabling highly sensitive detection and is being widely used in clinical settings for many different types of cancer, given the ease of use. 31,[33][34][35][36][37] However, CTCs may have different progenitors within tumors, which are heterogeneous in nature, and experimental pooling could mask cell-to-cell variations in expression that are biologically interesting and important. Recently, several reports charting the molecular heterogeneity of the CTCs population, [38][39][40] at single cell level, in breast, prostate and pancreatic cancer patients have been published.…”
Section: Ctcs: Transcriptomic Profilingmentioning
confidence: 99%
“…[30][31][32] RT-PCR analysis of CTCs signature, enabling highly sensitive detection and is being widely used in clinical settings for many different types of cancer, given the ease of use. 31,[33][34][35][36][37] However, CTCs may have different progenitors within tumors, which are heterogeneous in nature, and experimental pooling could mask cell-to-cell variations in expression that are biologically interesting and important. Recently, several reports charting the molecular heterogeneity of the CTCs population, [38][39][40] at single cell level, in breast, prostate and pancreatic cancer patients have been published.…”
Section: Ctcs: Transcriptomic Profilingmentioning
confidence: 99%
“…Another important and interesting point would be to decide by the RT-qPCR results whether a certain blood sample came from a cancer patient or was withdrawn from a healthy donor. But for this purpose, a lot of work still needs to be done, especially in defining a set of marker genes on which this decision could be made with high reliability [34,35,36]. The analysis of more marker genes like Her-2 [37], MMP13 [38], UBE2Q2 [39], or Nectin-4 [40] for their use in CTC detection could help in this point, allowing a more sensitive detection with simultaneous characterization of the tumor cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…both studies found, that cytokeratins are suitable PCR marker genes for CTC quantification from blood samples, promising new possibilities in CTC detection, treatment assessment and follow-up (152). The sensitivity of the CTC quantification could even be increased by a duplex PCR-assay, carried out subsequently after a negative enrichment (153).…”
Section: Recent Developments For Ctc Detection In Breast Cancermentioning
confidence: 99%